2020
DOI: 10.1515/ntrev-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis kinetics and mechanical properties of poly(lactic acid)/bamboo particle biocomposites: Effect of particle size distribution

Abstract: AbstractBamboo particle (BP)-reinforced poly(lactic acid) (PLA) biocomposites were fabricated. The effect of the BP particle size distribution on the pyrolysis and mechanical properties of PLA biocomposites was evaluated. The optimum particle size of BP for improving the tensile strength PLA biocomposites is 200 mesh (16.6–84.5 µm). The pyrolysis mechanism and kinetics were studied according to the Coats–Redfern method. The addition of BP inhibited the pyrolysis process of PLA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…Only 7.38% and 4% differences were found for char and gas yield between these selected particle sizes. is is similar to previous investigations [28][29][30], which found that if the particle size was small enough, the particle could be heated uniformly. is study revealed that mass-and heat-transfer constraints had a significant impact on oil yield at large particle sizes exceeding 1.0 mm, resulting in lower liquid yield.…”
Section: Influence Of Particle Sizesupporting
confidence: 92%
“…Only 7.38% and 4% differences were found for char and gas yield between these selected particle sizes. is is similar to previous investigations [28][29][30], which found that if the particle size was small enough, the particle could be heated uniformly. is study revealed that mass-and heat-transfer constraints had a significant impact on oil yield at large particle sizes exceeding 1.0 mm, resulting in lower liquid yield.…”
Section: Influence Of Particle Sizesupporting
confidence: 92%
“…Its role on the stent degradation could be included in our future work if quantitative experimental data are available. The mechanical properties and degradation behavior of the PLLA material could be influenced by its crystallinity degree, which was associated with the fabrication techniques [ 5 , 36 , 37 ]. This could be potentially used to regulate its degradation time.…”
Section: Discussionmentioning
confidence: 99%
“…Its elastic modulus is between 1.5-2.7 GPa and glass transition temperature is around 60 °C. Thus, PLA offers great mechanical properties, provides easy blending with many plasticizers to achieve desired rigidity [36]- [38]. In addition, stabilization properties of printed structure are very favorable.…”
Section: Less Flexibilitymentioning
confidence: 99%